Pembentukan Perilaku Peduli Lingkungan Hidup Desa Sitiaji Kabupaten Bojonegoro - Nindy Callista Elvania; Yenny Sri Margianti; Abilsa Duanda; Hesti Asriva; Bagus Saputra (UNIB Press, 2023)
Sitiaji Village is a village located far from the center of Bojonegoro City so that the village has never been socialized regarding environmental awareness by the relevant agencies. Even though currently the government of Bojonegoro Regency has implemented the